2020
DOI: 10.25165/j.ijabe.20201301.5031
|View full text |Cite
|
Sign up to set email alerts
|

Design of bionic locust mouthparts stubble cutting device

Abstract: Given the technical problems of low maize stubble breaking efficiency, large cutting torque and high power consumption faced during springtime no-till planting in Northeast China, we designed a high-performance coupling bionic stubble cutting device capable by integrating the structure (multi-segment and serrate) and cutting mode (isokinetic and symmetrical) of locust mouthparts. Methods of bionic construction, mechanism design, theoretical analysis, parameter optimization, Arduino systems and intelligent cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…To ensure that the disc cutter teeth are evenly distributed along the edge of the cutter head and avoid half teeth, a mathematical model of the disc cutter diameter and disc cutter teeth was established [13,26]:…”
Section: Bionic Design and Parameter Optimization Of Thementioning
confidence: 99%
“…To ensure that the disc cutter teeth are evenly distributed along the edge of the cutter head and avoid half teeth, a mathematical model of the disc cutter diameter and disc cutter teeth was established [13,26]:…”
Section: Bionic Design and Parameter Optimization Of Thementioning
confidence: 99%
“…The core operational performance of the straw returning machine is the cutting power consumption and crushing length qualification rate [21], so both were selected as test indicators. Numerous studies have shown that the two test indicators mainly depend on the rotational radius of the blade and the output rotation speed of the drive mechanism [26], so they are mainly optimized for both.…”
Section: Parameter Optimization Experiments Of Bionic Straw Returning Machine Based On Edem2018mentioning
confidence: 99%
“…The unique functions of organisms have been a source of creativity for humans to achieve technological breakthroughs [20]. Researchers studying an insect unique to northeastern China (primnoa, which feeds mainly on maize stalks) found that its mouthparts were far more efficient at cutting maize stalks than traditional straw returning blades [21]. The power consumption of the primnoa mouthparts gnawing on the corn rootstocks was only 23% of that of the traditional return blade [22].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have paid more and more attention to solve the problems in agricultural machinery through the principle of bionics. Studies have shown that the performance of agricultural machinery designed through bionics has been effectively improved [16,17] . Ma et al [18] designed a bionic non-smooth vibrating screen based on the characteristics of adhesion and resistance reduction of the bionic non-smooth surface and the function of hydrophobic self-cleaning of the biological surface, which revealed the mechanism of adhesion and resistance reduction of the cleaning screen surface.…”
Section: Introduction mentioning
confidence: 99%